2014
DOI: 10.1103/physrevstab.17.112805
|View full text |Cite
|
Sign up to set email alerts
|

Backward transition radiation in the extreme ultraviolet region as a tool for the transverse beam profile diagnostic

Abstract: The present article summarizes the results of two experiments which were performed to study the radiation properties of backward transition radiation (BTR) in the extreme ultraviolet (EUV) region. This wavelength region is of particular interest for transverse beam profile imaging, because the spatial resolution is improved as a result of the reduced contribution in the imaging process of the fundamental diffraction limit. In addition, the influence of coherent effects in the transition radiation emission proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In order to further increase the sensitivity to a level of sub-micron spatial resolution [18], the techniques proposed in the present work could in principle be combined with detection schemes at smaller wavelengths using OTR in the UV and EUV spectral region [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further increase the sensitivity to a level of sub-micron spatial resolution [18], the techniques proposed in the present work could in principle be combined with detection schemes at smaller wavelengths using OTR in the UV and EUV spectral region [19].…”
Section: Resultsmentioning
confidence: 99%
“…In Fig. 13 the results of a calculation for 0.5  (19) and this parameter is considered as the ultimate resolution of an imaging optics based on an ideal lens using isotropic light emission from a point source. For the following it is more convenient to compare the different PSF characteristics based on the FWHM (full width at half maximum).…”
Section: Discussionmentioning
confidence: 99%
“…In order to allow beam profile measurements in the presence of the instability, transition radiation based imaging in the EUV spectral region was successfully tested [385,386]. Another possibility which was demonstrated to work properly is to eliminate the COTR influence by using a fast gated camera in combination with a scintillator screen (so-called temporal separation) [387,388].…”
Section: Instrumentation Examplesmentioning
confidence: 99%
“…In Refs. [17,18] it was demonstrated that backward transition radiation in the extreme ultraviolet (EUV) spectral region (λ ≈ 19 nm) can be used for beam profile imaging. While EUV transition radiation has sufficient intensity for beam diagnostics applications, the main disadvantage in this spectral region is the strong radiation absorption in any material, making it necessary to install the entire monitor setup in a vacuum system.…”
Section: Introductionmentioning
confidence: 99%